Tanggungjawab pemunya dan pemilik haiwan dalam undang-undang tort Islam - Abdul Basir Mohamad (Penerbit Universiti Kebangsaan Malaysia, 1999)
Tort wrongs can exist either through the deeds of human beings or inanimate beings and also animals. If an injury or death has occurred through the acts of an inanimate being or animal, its owner or keeper should be identified. Islamic law primarily takes care of this matter, and it can be seen that all ulama of sunni schools of Islam discussing it in their manuscripts. Likewise, it has been codified into a few civil laws of Arab countries. Islam gives permission that every person can rear animals, however he is required to monitor such animals properly so that they do not break loose and move on their own accord, and trespass to another person or his property. This action is actually to take care of the right of individuals in society and respecting their blood and life in order to not being easily transgressed. As a result, peace and harmony will be established in the society